Whole-genome comparison using complete genomes from Campylobacter fetus strains revealed single nucleotide polymorphisms on non-genomic islands for subspecies differentiation - Ong, Chian Teng; Blackall, Patrick. J.; Boe-Hansen, Gry B.; deWet, Sharon; Hayes, Ben J.; Indjein, Lea; Korolik, Victoria; Minchin, Catherine; Nguyen, Loan To; Nordin, Yusralimuna; Siddle, Hannah; Turni, Conny; et al. (Frontiers in Microbiology, 2024)
Bovine Genital Campylobacteriosis (BGC), caused by Campylobacter fetus subsp. venerealis, is a sexually transmitted bacterium that significantly impacts cattle reproductive performance.However, current detection methods lack consistency and reliability due to the close genetic similarity between C. fetus subsp. venerealis and C. fetus subsp. fetus. This study aimed to use complete genome analysis to distinguish genetic features between C. fetus subsp. venerealis and other subspecies, thereby enhancing BGC detection for routine screening and epidemiological studies. This study reported 4 C. fetus subsp. fetus and 5 C. fetus subsp.venerealis complete genomes sequenced using long-read sequencing technologies.Comparative whole-genome analyses (n=25) were conducted with an additional 16 complete C. fetus genomes from NCBI database to investigate the genomic differences in the two closely related C. fetus subspecies. The pan-genomic analyses revealed a core genome of 1,561 genes and an accessory pangenome of 1,064 genes between the two C. fetus subspecies. However, no unique predicted genes were identified in either of the subspecies. Nonetheless, the wholegenome single nucleotide polymorphisms (SNPs) analysis identified 289 SNPs that were unique to either of the C. fetus subspecies. After the removal of SNPs located on putative genomic islands, recombination sites and SNPs causing synonymous amino acid changes, the encoded genes of the remaining SNPs (n=184) were functionally annotated. Candidate SNPs which were annotated with KEGG "Peptidoglycan Biosynthesis" pathway were recruited for further analysis because of their potential association to the glycine intolerance feature of C. fetus subsp. venerealis and its biovar variant. Verification with 58 annotated C. fetus genomes, both complete and incomplete, from RefSeq successfully classified these 7 SNPs into two groups, CFF or CFV/CFVi, aligning with their phenotypic identification. Furthermore, we demonstrated the application of mraY SNPs for detecting C. fetus subspecies using a quantitative PCR assay. Our results demonstrated the high genetic stability of C. fetus subspecies. Nevertheless, Campylobacter fetus subsp. venerealis and its biovar variants encoded common SNPs in genes relating to glycine intolerance, distinguishing them from C. fetus subsp. fetus. This discovery underscores the promising potential of employing a multiple-SNP assay for the differentiation of C. fetus subspecies.